ANALYSING FACTORS THAT DRIVES CUSTOMER LOYALTY OF SHOES LAUNDRY QUICKCARES MANADO - Mawa, Maria .; Tumbuan, Willem J.F.Alfa; Tielung, Maria V.J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract:This research is to analyzing what are the factors that drive customer loyalty of shoe laundry Quickcares Manado. Shoe Laundry is the services that offer to clean and taking care shoe, Customer Loyalty is the result of consistently positive emotional experience, physical attribute-based satisfaction and perceived value of an experience, which includes the product or services. It is important to know factors that drive customer Loyalty in business, in order to guarantee business continuity and to survive from business competition. Quantitative research seeks to quantify the data. Data was collected using questionnaire that distributed to 100 people that already used the services as respondents. The Factor Analysis method is used in this research. The analysis and discussion from this research there are 19 variables that correlated with the factor that already conducted. The findings from the factoring process there are 2 factors that drive customer loyalty of Shoe Laundry Quickcares Manado. First factor is Service Quality with 12 independent variables (Customer satisfaction, Brand Image, Tangibility, Responsiveness, Assurance, Empathy, Reliability, Corporate Reputation, Waiting Time, Trends, Customer Experience, Trust) and the second factor is Customer Decision Making with 7 independent variables (Innovation, Price, Place, Promotion, Switching Cost, Instrumental Commitment, Rational Commitment)Keywords: shoes laundry, customer loyalty, factor analysis.